The Most Frequently Used Arguments for Increasing Women’sParticipation in Justice - (:unkn) unknown (My University, 2016)
This document develops two main arguments, which the author uses to elaborate discussions of theinclusion of women judges in the area of judicial administration. The two main topics are democraticlegitimacy (disadvantaged groups) and the specific contribution that women can make to justice if theirparticipation in the justice system is increased.The author provides evidence so support both claims, arguing for equality for women in justice and thesignificant amount of consensus that exists in this area in societies that are based on the principle ofdemocratic equality.